Generation of Mammalian Cells Devoid of Mitochondrial DNA (ρ0 cells). Issue 2 (21st February 2023) - Khozhukhar, Natalya; Spadafora, Domenico; Rodriguez, Yelitza A. Rodriguez; Fayzulin, Rafik; Alexeyev, Mikhail
Abstract: To cope with DNA damage, mitochondria have developed a pathway whereby severely damaged or unrepairable mitochondrial DNA (mtDNA) molecules can be discarded and degraded, after which new molecules are synthesized using intact templates. In this unit, we describe a method that harnesses this pathway to eliminate mtDNA from mammalian cells by transiently overexpressing the Y147A mutant of human uracil‐ N ‐glycosylase (mUNG1) in mitochondria. We also provide alternate protocols for mtDNA elimination using either combined treatment with ethidium bromide (EtBr) and dideoxycytidine (ddC) or clustered regulatory interspersed short palindromic repeat (CRISPR)‐Cas9‐mediated knockout of TFAM or other genes essential for mtDNA replication. Support protocols detail approaches for several processes: (1) genotyping ρ 0 cells of human, mouse, and rat origin by polymerase chain reaction (PCR); (2) quantification of mtDNA by quantitative PCR (qPCR); (3) preparation of calibrator plasmids for mtDNA quantification; and (4) quantification of mtDNA by direct droplet digital PCR (dddPCR). © 2023 Wiley Periodicals LLC. Basic Protocol : Inducing mtDNA loss with mUNG1 Alternate Protocol 1 : Generation of ρ 0 cells by mtDNA depletion with EtBr and ddC Alternate Protocol 2 : Generation of ρ 0 cells by knocking out genes critical for mtDNA replication Support Protocol 1 : Genotyping ρ 0 cells by DirectPCR Support Protocol 2 : Determination of mtDNA copy number by qPCR Support Protocol 3 : Preparation of calibrator plasmid for qPCR Support Protocol 4 : Determination of mtCN by direct droplet digital PCR (dddPCR)